An Examination of the Customer and Product Data Bill: Leveraging Australia’s Lessons - Ward, Ciaran (Victoria University of Wellington Law Review, 2025)
The implementation of a Consumer Data Right (CDR) in Australia has pioneered an economy-wide data portability framework, setting a precedent for others to follow. New Zealand is poised to adopt a similar model, and in May 2024 introduced the New Zealand Customer and Product Data Bill to its House of Representatives. This article offers an overview of the CDR and evaluates whether New Zealand’s legal framework and implementation strategies can circumvent the hurdles that have impeded the CDR’s adoption in Australia. Ultimately, the author argues that without sufficient industry and consumer participation, the CDR’s efficacy and long-term viability are at risk – concessions must be made to ensure the CDR attracts both customers and industry players. This article considers action initiation, the decision to utilise existing Privacy Act 2020 Information Privacy Principles (IPPs), the exclusion of reciprocal data sharing and the considerations of Māori data and Māori data governance.